The answer is 196 This is the answer to ur question
Thank you for posting
your question here at brainly. Feel free to ask more questions.
f′(x)=2∗(8x(2−1))+1∗11x(1−1)
which is
f′(x)=16x+11
then let
x = 7 gives us
f′(7)=123
<span>
<span>Hope my answer would be a great help for you. </span> </span>
<span> </span>
132 or 2.304 radian ? still not really sure what's being asked
F(x) = 3x + 2x = 3f-1(x) + 2x - 2 = 3f-1(x)(x - 2)/3 = f-1(x)(14 - 2)/3 = f-1(14)12/3 = f-1(14)4 = f-1(14) f(f-1(14)) = f(4)f(4) = 3(4) + 2f(4) = 12 + 2f(4) = 14 A function and its inverse are inverse operations, like addition and subtraction. They undo each other. f(f-1(x) = x
Answer:
10
Step-by-step explanation:
If Sabrina is 5 & Michael is 7. (5×7=35)
Michael is 7, & he is 3 yrs younger than Meghan, who is 10. And Meghan is twice as old as Sabrina, when Sabrina is 5 (5×2=10).